Alkenyl Arenes as Dipolarophiles in Catalytic Asymmetric 1, 3‐Dipolar Cycloaddition Reactions of Azomethine Ylides. (11th November 2016) - Pascual‐Escudero, Ana; de Cózar, Abel; Cossío, Fernando P.; Adrio, Javier; Carretero, Juan C.
Abstract: The use of alkenyl arenes as dipolarophiles in the catalytic asymmetric 1, 3‐dipolar cycloaddition of azomethine ylides is reported. Under appropriate reaction conditions with a Cu I or Ag I catalyst either the exo or the endo adduct was obtained with high stereoselectivity. This process provides efficient access to highly enantiomerically enriched 4‐aryl proline derivatives. The observed results are compatible with the blockage of one prochiral face of the 1, 3‐dipole, as well as with the efficient transmission of electrophilicity towards the terminal carbon atom of the dipolarophile. This polarization results in a change from a concerted to a stepwise mechanism.